A Review of the Botanical, Conventional Applications, Phytochemical Constituents, and Pharmacology of Madhuca longifolia (Koenig) J.F. Macb - Dubey, Ishan; Chhajed, Mahavir; Chourasiya, Rashmi; Chouhan, Pallavi Singh; Walvekar, Amruta; Bhandari, Yash; Verma, Kiran (Pharmacognosy Reviews)
In underdeveloped countries, between 75 and 80 percent of the world's population still significantly relies on herbal medicine for primary treatment. Madhuca longifolia (Mahua), commonly referred to as butternut tree, is a species of tree significant to the daily life of tribal people. It belongs to the Sapotaceae family, a significant economic tree that is spread over the sub-tropical Indo-Pak peninsula. A large to medium-sized deciduous tree with a short bole and a broad, rounded crown, the mahua tree typically possesses these characteristics. A phytochemical analysis of the plant M. longifolia revealed the presence of several secondary metabolites, including sapogenins, triterpenoids, saponins, flavonoids, and glycosides. These substances exhibit notable antidiabetic, antiulcer, antioxidant, antipyretic, hepatoprotective, anti-inflammatory, analgesic, anti-tumor, anti-progestational, anti-estrogenic, wound healing activity, rheumatism, ulcers, bleedings, tonsillitis, swelling, inflammation, piles, emetic, dermatological, laxative, tonic, anti-burn, anti-earthworm, headache and many more problems. In this review, we explore the many traditional and an ethnomedical use of the bark, fruit, flower, and leaves of M. longifolia. These studies' findings have emphasised Mahua's present pharmacological profile and effectively demonstrated its potential for therapeutic use in modern medicine.
Keywords: Madhuca longifolia; Phytoconstituents; Pharmacological activity; Traditional medicines; Herbs